The role of clinical and immunological parameters in predicting the effectiveness of additional immunotropic therapy in oxygen-dependent patients with COVID-19 coronavirus disease - O. V. Riabokon; V. V. Cherkaskyi; Yu. Yu. Riabokon; A. V. Vynokurova (Patologìâ)
Aim. The purpose of the research is to find out the role of clinical and immunological parameters in predicting the effectiveness of additional immunotropic therapy in oxygen-dependent patients with the coronavirus disease COVID-19.